Investigating the Effectiveness of Using Blended Learning on Grade Ten (16-year-old) ESL Learners' Lexical Range and Accuracy - KAMEL, MOHAMED HASSAN MOHAMED (2023)
The digital age has revolutionised the landscape of education, prompting a shift from traditional teaching methods to innovative approaches. This dissertation delves into the transformative potential of blended learning, focusing on its impact on the vocabulary range and accuracy of grade 10 students. The central objective of this study was to meticulously explore how blended learning influences students' vocabulary skills and their perceptions towards this blended educational model. Employing a comprehensive mixed-methods approach, this research integrated quantitative and qualitative data collection methods. Two sets of pre- and post-tests were administered, allowing for a quantitative assessment of the students' vocabulary acquisition. Furthermore, qualitative insights were gathered through in-depth interviews, providing a nuanced understanding of the students' attitudes and experiences with blended learning. The outcomes of this study revealed compelling evidence in favour of blended learning. The students engaged in blended learning activities exhibited a substantial improvement in their vocabulary range and accuracy compared to their counterparts exposed to traditional teaching methods. Moreover, the qualitative findings illuminated the positive attitudes students held towards blended learning, emphasising its interactive and engaging nature. This research has significant implications for both educators and curriculum designers. For educators, the study serves as a valuable guidepost, showcasing the effectiveness of blended learning in enhancing students' vocabulary skills. By integrating blended learning strategies, educators can create dynamic learning environments that cater to diverse learning styles, fostering improved vocabulary acquisition among students. Curriculum designers can draw upon these findings to develop innovative and adaptive curricula, aligning educational objectives with the interactive potential of blended learning. In essence, this dissertation not only contributes empirical evidence to the discourse on blended learning, but also underscores its potential as a catalyst for educational advancement. By embracing the insights presented in this study, educators and curriculum designers are empowered to reshape the educational landscape, ensuring a more engaging and effective learning experience for students.